Pengaruh Akuntabilitas, Pengalaman Kerja dan Independensi Auditor Terhadap Kualitas Audit dengan Etika Auditor Sebagai Variabel Moderasi (Studi Empiris pada Kantor Akuntan Publik di Wilayah Surakarta dan Yogyakarta) - Nursyahbani, Fivit; , Drs. Wahyono, Ak, MA (2016)
The purpose of this study was to examine the effect of accountability, work experience and independence of the audit quality with the auditor ethics as moderating variables. This study was conducted by using survey method with questionnaire. The population in this study is the auditor of KAP in the Surakarta dan Yogyakarta. Determination of sample, using a convience sampling and obtained a sample of 40 respondents. Data analysis was conducted using multiple regression model and Moderated Regression Analysis (MRA). These results prove that the accountability, work experience, auditor independence and ethics of positive and significant impact on audit quality. Interaction of work experience and ethics compliance auditor positive and significant effect on audit quality. Interaction accountability and ethics compliance, as well as the interaction of ethics compliance auditor's independence and has no effect on audit quality. Value determination coefficient of 0.662. This means that 66.2% of audit quality variable variation can be explained by the variable accountability, work experience variable, the variable independence, as well as interaction variables accountability and ethics of auditors, variable interactions work experience and ethics of auditors, variable interactions auditor independence and ethics, while the remaining 33.8% is explained by other factors outside the model studied. studied.